Health of the War Worker (London : Labour Research Department)
1942-04 1942 1940s 44 pages ments concerned. Particulars of how to do this will be found in the L.R.D. pamphlet quoted above. Meals in Dangerous Trades Factories Act. Section 48 (1). Where in any room lead, arsenic, or other poisonous substance is so used as to give rise to any dust or fume, a person shall not be permitted to partake of food or drink in that room or to remain in that room during the intervals allowed to him for meals or rest other than intervals allowed in the course of a spell of continuous employment. The management must provide a suitable room elsewhere for employees in these circumstances to take their meals. This is a very difficult section of the Act to get properly enforced, in spite of its great importance. Workers themselves are often very slack about making use of the alternative accommodation and do not show sufficient appreciation of the dangers involved by eating in rooms where poisonous substances may lie around. Although messrooms are not required in other trades, no worker should be obliged to eat his dinner in the workshop. From the general health viewpoint, a place where food can be eaten and warmed up is needed in every factory, and it is usually possible to find a suitable room for the purpose. Milk Milk is required to be provided by law only for certain workers in the pottery industry. It cannot be legally enforced in any other trade. It has been provided elsewhere often by agreement between the managements and the workers and where this agreement has been arrived at, while milk is unrationed, every effort should be made to maintain this supply to the workers, for milk is probably the finest all-round food and it is therefore of importance to swallow it whenever opportunity offers. The valuable properties of milk as a diet, however, can be obtained by adults from other foods, but cannot be obtained by infants nearly so easily. When milk is very short, therefore, it is correct policy to supply infants and children before workers. Protective clothing Accidents and ill-health can be greatly reduced by the provision of suitable protective clothing. This includes ordinary overalls and caps to guard against clothing or hair catching in machinery, 11 21/2049